Perlindungan Hukum terhadap Pekerja Usia Anak di Indonesia - Azali, Nur Azkiya; Zahratul Aini; Putri Anggun Sari; Ilham Hudi; M. Irfan Wahyudi; Chandra Halim (Lembag, 2024)
The existence of child exploitation and child labor will add to labor problems in Indonesia. The term